Analysis of apolipoprotein genes and their involvement in disease response of channel catfish after bacterial infection. (February 2017) - Yang, Yujia; Fu, Qiang; Zhou, Tao; Li, Yun; Liu, Shikai; Zeng, Qifan; Wang, Xiaozhu; Jin, Yulin; Tian, Changxu; Qin, Zhenkui; Dunham, Rex; Liu, Zhanjiang
Abstract: Apolipoproteins are protein component of plasma lipoproteins. They exert crucial roles in lipoprotein metabolism and serve as enzyme cofactors, receptor ligands, and lipid transfer carriers in mammals. In teleosts, apolipoproteins are also involved in diverse processes including embryonic and ontogenic development, liver and digestive system organogenesis, and innate immunity. In this study, we identified a set of 19 apolipoprotein genes in channel catfish ( Ictalurus punctatus ). Phylogenetic analysis and syntenic analysis were conducted to determine their identities and evolutionary relationships. The expression signatures of apolipoproteins in channel catfish were determined in healthy tissues and after infections with two major bacterial pathogens, Edwardsiella ictaluri and Flavobacterium columnare . In healthy channel catfish, most apolipoprotein genes exhibited tissue-specific expression patterns in channel catfish. After ESC and columnaris infections, 5 and 7 apolipoprotein genes were differentially expressed respectively, which presented a pathogen-specific and time-dependent pattern of regulation. After ESC infection, three exchangeable apolipoproteins (apoA-IB, apoC-I, and apoE-B) were suppressed in catfish intestine, while two nonexchangeable apolipoproteins (apoB-A and apoB-B) were slightly up-regulated. After columnaris infection, apoB-B, apoD-B, and apoE-A were significantly down-regulated in catfish gill, while apoF, apoL-IV, apoO-like, and apo-14 kDa showed significantly up-regulation. Taken together, these results suggested that apolipoprotein genes may play significant roles in innate immune responses to bacterial pathogens in channel catfish. Highlights: A complete set of 19 apolipoprotein genes were identified in channel catfish. The 19 apolipoprotein genes were annotated by phylogenetic and syntenic analysis. Differentially expressed apolipoprotein genes were identified after bacterial infections.